CURABLE RESIN COMPOSITION, DRY FILM, CURED PRODUCT, AND PRINTED WIRING BOARD
Patent Information
- Application Number
- JP2020072546
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-04-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-04-14
Smart Images

Figure 0007634345000001 
Figure 0007634345000002 
Figure 0007634345000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition, a dry film, a cured product, and a printed wiring board. [Background technology]
[0002] In the manufacture of printed wiring boards, curable resin compositions are generally used to form permanent coatings such as solder resists, and dry film-type compositions and liquid compositions have been developed as such curable resin compositions. Among these, in consideration of environmental issues, alkaline development-type curable resin compositions that use a dilute alkaline aqueous solution as a developer have become mainstream, and several composition systems have been proposed in the past (e.g., Patent Document 1).
[0003] In recent years, due to the rapid progress of semiconductor parts, electronic devices tend to become lighter, thinner, shorter, smaller, more powerful, and more multifunctional. Following this trend, miniaturization and increased pin count of semiconductor packages have been put into practical use. Specifically, IC packages called BGA (ball grid array), CSP (chip scale package), etc. are being used instead of IC packages called QFP (quad flat pack package) and SOP (small outline package). In addition, FC-BGA (flip chip ball grid array) has also been put into practical use as an IC package with higher density in recent years. There is a demand for even thinner permanent coatings such as solder resist formed on printed wiring boards (also called package substrates) used in such IC packages. Furthermore, from the viewpoints of hiding power and design, solder resists are sometimes required to be black in color. For this reason, curable resin compositions used in solder resists include those that contain carbon black, which exhibits a black color, as a colorant, and those that exhibit a black color by containing a combination of pigments of multiple colors other than black. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 61-243869 A (Claims) Summary of the Invention [Problem to be solved by the invention]
[0005] Current solder resists are often photocured to form an image, and then heat cured. This heat curing process can cause the copper circuit to discolor due to oxidation. In addition, when marking ink is applied to a substrate, the marking is printed and heat cured after the solder resist is cured, so the discoloration of the copper circuit can be accelerated. Furthermore, pressure and heat may be applied to correct the warping of the substrate that occurs during the heat curing of the solder resist, and the circuit may also be discolored. This discoloration could not be completely concealed by conventional black curable resin compositions, and the appearance of the substrate may be poor. In addition, even conventional curable resin compositions containing a blue colorant to show black in combination with the copper color of the copper circuit do not have sufficient concealing properties, and in particular, there is still room for improvement in the concealing properties of copper circuits that have been subjected to CZ treatment, which is a treatment for roughening the copper surface and increasing adhesion. Furthermore, solder resist must avoid, wherever possible, any reduction in resolution due to the incorporation of colorants, and is required to achieve both high levels of hiding power and resolution. In the past, however, it was necessary to change components other than the color tone, and when prioritizing resolution, it was necessary to reduce the amount of black pigment added, which ensured hiding power. In this case, depending on the curing conditions, the color tone would change due to oxidation of the copper circuit.
[0006] Therefore, an object of the present invention is to provide an alkali-developable curable resin composition which forms a coating film on copper after CZ treatment that has excellent hiding properties and therefore changes little in color after heating, and which has excellent resolution; a dry film having a resin layer obtained from the composition; a cured product of the composition or the resin layer of the dry film; and a printed wiring board having the cured product. [Means for solving the problem]
[0007] In view of the above, the inventors conducted intensive research and found that a curable resin composition having a transmittance within a predetermined range under specific test conditions forms a coating film on copper after CZ treatment that has excellent hiding properties, resulting in little change in color after heating and excellent resolution, and thus led to the completion of the present invention.
[0008] That is, the curable resin composition of the present invention contains (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, and is formed on copper having a CZ-treated surface, The curable resin composition is characterized in that the dry coating film (film thickness: 20 μm) formed on a glass substrate with a thickness of 2 mm has a transmittance of 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm.
[0009] In the curable resin composition of the present invention, the dry coating film preferably has a transmittance of 12% or less at a wavelength of 720 nm.
[0010] In the curable resin composition of the present invention, the dry coating film preferably has a transmittance of 5% or more at a wavelength of 365 nm.
[0011] The dry film of the present invention is characterized by having a resin layer obtained from the above-mentioned curable resin composition.
[0012] The cured product of the present invention is characterized by being obtained by curing the curable resin composition or the resin layer of the dry film.
[0013] The printed wiring board of the present invention is characterized by comprising the above-mentioned cured product. Effect of the Invention
[0014] According to the present invention, it is possible to provide an alkali-developable curable resin composition which has excellent resolution and which exhibits little change in color after heating due to its excellent hiding property as a coating film formed on copper after CZ treatment; a dry film having a resin layer obtained from the composition; a cured product of the composition or the resin layer of the dry film; and a printed wiring board having the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The curable resin composition of the present invention contains (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, and is formed on copper having a CZ-treated surface, The transmittance of a dry coating film (film thickness 20 μm) of the curable resin composition formed on a glass substrate having a thickness of 2 mm is 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm. In one example, the blending ratio of the red colorant, yellow colorant, blue colorant, and black colorant in the curable resin composition is adjusted so that the transmittance of the coating film tested on a glass substrate having a thickness of 2 mm is 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm. The curable resin composition having such transmittance is neither a conventional black curable resin composition nor a conventional blue curable resin composition, but a novel curable resin composition, and although it is difficult to specify it by the blending ratio of the colorant, the composition having a dry coating film (film thickness 20 μm) of the curable resin composition formed on a glass substrate having a thickness of 2 mm and having a transmittance of 30 to 50% at a wavelength of 430 nm and 28 to 45% at a wavelength of 530 nm has both the hiding power and resolution desired in the present invention. Therefore, the curable resin composition of the present invention is specified to have a transmittance in a predetermined range under specific test conditions. The transmittance is measured by forming a dry coating film of the curable resin composition on a 2 mm thick glass substrate with an applicator so that the film has a thickness of 20 μm after drying at 80° C. for 30 minutes, or by laminating a 20 μm thick dry film on a 2 mm thick glass substrate and peeling off the carrier film. The transmittance is measured with a UV-Visible-Near-Infrared Spectrophotometer V-670 (manufactured by JASCO Corporation). Preferably, the transmittance of the dried coating film is 12% or less at a wavelength of 720 nm, which makes it possible to minimize changes in color tone after heat treatment. Also preferably, the transmittance of the dried coating film is 5% or more at a wavelength of 365 nm, which can improve the resolution.
[0016] Each component of the curable resin composition of the present invention will be described below. In this specification, (meth)acrylate is a term that collectively refers to acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions.
[0017] [(A) Alkali-soluble resin] (A) Examples of the alkali-soluble resin include a compound having two or more phenolic hydroxyl groups, a carboxyl group-containing resin, a compound having a phenolic hydroxyl group and a carboxyl group, and a compound having two or more thiol groups. Among them, it is preferable that the alkali-soluble resin is a carboxyl group-containing resin or a phenolic resin, since the adhesion to the base is improved. In particular, it is more preferable that the alkali-soluble resin is a carboxyl group-containing resin, since it has excellent developability. The carboxyl group-containing resin is preferably a carboxyl group-containing photosensitive resin having an ethylenically unsaturated double bond, but may be a carboxyl group-containing resin without an ethylenically unsaturated double bond.
[0018] Specific examples of the carboxyl group-containing resin include the compounds (which may be either oligomers or polymers) listed below.
[0019] (1) Carboxyl group-containing resins obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, isobutylene, etc.
[0020] (2) Carboxyl group-containing urethane resins obtained by the polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0021] (3) Terminal carboxyl group-containing urethane resins obtained by reacting acid anhydrides with the terminals of urethane resins obtained by polyaddition reaction of diisocyanate compounds such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.
[0022] (4) Carboxyl group-containing urethane resins obtained by polyaddition reaction of diisocyanates with (meth)acrylates of bifunctional epoxy resins such as bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bixylenol type epoxy resins, and biphenol type epoxy resins, or their partial acid anhydride modified products, carboxyl group-containing dialcohol compounds, and diol compounds.
[0023] (5) A carboxyl group-containing urethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as a hydroxyalkyl (meth)acrylate, during the synthesis of the resin (2) or (4) above, to obtain a terminal (meth)acrylated carboxyl group-containing urethane resin.
[0024] (6) A carboxyl group-containing urethane resin having terminal (meth)acrylation obtained by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reactant of isophorone diisocyanate and pentaerythritol triacrylate, during the synthesis of the resin (2) or (4) above.
[0025] (7) Carboxyl group-containing resins obtained by reacting a multifunctional epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chains.
[0026] (8) A carboxyl group-containing resin obtained by reacting a multifunctional epoxy resin with the hydroxyl groups of a difunctional epoxy resin further epoxidized with epichlorohydrin, with (meth)acrylic acid, and adding a dibasic acid anhydride to the resulting hydroxyl groups.
[0027] (9) A carboxyl group-containing polyester resin obtained by reacting a polyfunctional oxetane resin with a dicarboxylic acid and adding a dibasic acid anhydride to the resulting primary hydroxyl group.
[0028] (10) A carboxyl group-containing resin obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with an alkylene oxide such as ethylene oxide or propylene oxide, reacting the reaction product obtained with an unsaturated group-containing monocarboxylic acid, and reacting the resulting reaction product with a polybasic acid anhydride.
[0029] (11) A carboxyl group-containing resin obtained by reacting a compound having multiple phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the reaction product obtained with an unsaturated group-containing monocarboxylic acid, and reacting the resulting reaction product with a polybasic acid anhydride.
[0030] (12) A carboxyl group-containing resin obtained by reacting an epoxy compound having multiple epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenethyl alcohol, and an unsaturated group-containing monocarboxylic acid, such as (meth)acrylic acid, and then reacting the alcoholic hydroxyl group of the resulting reaction product with a polybasic acid anhydride, such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, adipic anhydride, or the like.
[0031] (13) A carboxyl group-containing resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, to the carboxyl group-containing resin described in the above (1) to (12), etc.
[0032] Among the above carboxyl group-containing resins, the carboxyl group-containing resins described in (1), (7), (8), and (10) to (13) are preferred.
[0033] Examples of compounds having a phenolic hydroxyl group include compounds having a biphenyl skeleton or a phenylene skeleton, or both of these skeletons, and phenol resins having various skeletons synthesized using phenol, orthocresol, paracresol, metacresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, catechol, resorcinol, hydroquinone, methylhydroquinone, 2,6-dimethylhydroquinone, trimethylhydroquinone, pyrogallol, phloroglucinol, etc.
[0034] Examples of the compound having a phenolic hydroxyl group include well-known and commonly used phenolic resins such as phenol novolak resin, alkylphenol volak resin, bisphenol A novolak resin, dicyclopentadiene type phenolic resin, Xylok type phenolic resin, terpene modified phenolic resin, polyvinylphenols, bisphenol F, bisphenol S type phenolic resin, poly-p-hydroxystyrene, condensates of naphthol and aldehydes, and condensates of dihydroxynaphthalene and aldehydes.
[0035] Commercially available phenolic resins include, for example, HF1H60 (manufactured by Meiwa Chemical Industry Co., Ltd.), Phenolite TD-2090, Phenolite TD-2131 (manufactured by DIC Corporation), Besumor CZ-256-A (manufactured by DIC Corporation), Shownol BRG-555, Shownol BRG-556 (manufactured by Aica Kogyo Co., Ltd.), and polyvinylphenols CST70, CST90, S-1P, and S-2P (manufactured by Maruzen Oil Co., Ltd.).
[0036] The acid value of the alkali-soluble resin (A) is preferably in the range of 40 to 200 mgKOH / g, more preferably 45 to 120 mgKOH / g. If the acid value of the alkali-soluble resin is 40 mgKOH / g or more, alkaline development becomes easy, while if it is 200 mgKOH / g or less, drawing of a normal resist pattern becomes easy, so this is preferable.
[0037] The weight-average molecular weight of the alkali-soluble resin (A) varies depending on the resin skeleton, but is preferably in the range of 1,500 to 150,000, more preferably 1,500 to 100,000. When the weight-average molecular weight is 1,500 or more, the tack-free performance is good, the moisture resistance of the coating film after exposure is good, and the film loss during development is suppressed, and the decrease in resolution can be suppressed. On the other hand, when the weight-average molecular weight is 150,000 or less, the developability is good and the storage stability is also excellent.
[0038] (A) The alkali-soluble resin may be used alone or in combination of two or more. can.
[0039] [(B) Photopolymerization initiator] In the curable resin composition of the present invention, any photopolymerization initiator known as a photopolymerization initiator or photoradical generator may be used as the photopolymerization initiator (B). Examples of the photopolymerization initiator (B) include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad, manufactured by IGM Resins). 819) and other bisacylphosphine oxides; 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine acid methyl ester, 2-methylbenzoyldiphenylphosphine oxide, pivaloylphenylphosphine acid isopropyl ester, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (Omnirad TPO manufactured by IGM Resins), H) and other monoacylphosphine oxides; hydroxyacetophenones such as 1-hydroxy-cyclohexyl phenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and 2-hydroxy-2-methyl-1-phenylpropan-1-one; benzoins such as benzoin, benzil, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, and benzoin n-butyl ether; benzoin alkyl ethers;Benzophenone, p-methylbenzophenone, Michler's ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bisdiethylaminobenzophenone and other benzophenones; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2 -Dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-butanone, N,N-dimethylaminoacetophenone and other acetophenones; thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-diisopropylthioxanthone and other thioxanthones; anthraquinones such as anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, and 2-aminoanthraquinone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzoic acid esters such as ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoic acid ethyl ester; 1,2-octanedione, 1-[4 -(phenylthio)-, 2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime) and other oxime esters; bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl)titanium, bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-pyr-1-yl)ethyl)phenyl]titanium and other titanocenes;Examples of the photopolymerization initiator include phenyl disulfide 2-nitrofluorene, butyroin, anisoin ethyl ether, azobisisobutyronitrile, and tetramethylthiuram disulfide. The photopolymerization initiator may be used alone or in combination of two or more. Among them, oxime esters (hereinafter also referred to as "oxime ester photopolymerization initiators") are preferred, and ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, and 1-(O-acetyloxime) are more preferred. The blending amount of the (B) photopolymerization initiator is, for example, 0.01 to 30 parts by mass relative to 100 parts by mass of the solid content of the (A) alkali-soluble resin. The blending amount of the oxime ester photopolymerization initiator is preferably 8% by mass or more, more preferably 12% by mass or more, calculated as solid content based on the total amount of the photopolymerization initiator. By containing 8% by mass or more, high sensitivity can be easily achieved. The oxime ester photopolymerization initiator can be used alone or in combination of two or more kinds.
[0040] Any known oxime ester photopolymerization initiator can be used as the oxime ester photopolymerization initiator. Commercially available products include Irgacure OXE01 (1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)]) and Irgacure OXE02 (ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime)) manufactured by BASF Japan Co., Ltd., N-1919 and NCI-831 manufactured by ADEKA Co., Ltd., and TR-PBG-304 manufactured by Changzhou Strong Electronic New Materials Co., Ltd.
[0041] In addition, an initiator having two oxime ester groups in the molecule can also be suitably used. Specific examples thereof include oxime ester compounds having a carbazole structure represented by the following general formula. TIFF0007634345000001.tif48170 (wherein X represents a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a phenyl group, a phenyl group (substituted with an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having 1 to 8 carbon atoms, or a dialkylamino group), a naphthyl group (substituted with an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having 1 to 8 carbon atoms, or a dialkylamino group), and Y and Z represent a hydrogen atom, an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, a halogen group, a phenyl group, a phenyl group (substituted with an alkyl group having 1 to 17 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an amino group, an alkylamino group having 1 to 8 carbon atoms, or a dialkylamino group), Ar represents a bond or an alkylene having 1 to 10 carbon atoms, vinylene, phenylene, biphenylene, pyridylene, naphthylene, thiophene, anthrylene, thienylene, furylene, 2,5-pyrrole-diyl, 4,4'-stilbene-diyl, or 4,2'-styrene-diyl; and n is an integer of 0 or 1.
[0042] In particular, in the above general formula, it is preferred that X and Y are each a methyl group or an ethyl group, Z is a methyl group or a phenyl group, n is 0, and Ar is a bond, phenylene, naphthylene, thiophene, or thienylene.
[0043] Further, preferred carbazole oxime ester compounds include compounds represented by the following general formula: TIFF0007634345000002.tif52170 (in the formula, R 1represents an alkyl group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with a nitro group, a halogen atom, or an alkyl group having 1 to 4 carbon atoms. R 2 represents an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a phenyl group which may be substituted with an alkyl group or alkoxy group having 1 to 4 carbon atoms. R 3 represents an alkyl group having 1 to 20 carbon atoms which may be linked via an oxygen atom or a sulfur atom and which may be substituted with a phenyl group, or a benzyl group which may be substituted with an alkoxy group having 1 to 4 carbon atoms. R 4 represents a nitro group or an acyl group represented by XC(=O)-. X represents an aryl group which may be substituted with an alkyl group having 1 to 4 carbon atoms, a thienyl group, a morpholino group, a thiophenyl group, or a structure represented by the following formula: TIFF0007634345000003.tif18170
[0044] Other examples include carbazole oxime ester compounds described in JP-A-2004-359639, JP-A-2005-097141, JP-A-2005-220097, JP-A-2006-160634, JP-A-2008-094770, JP-T-2008-509967, JP-A-2009-040762, and JP-A-2011-80036.
[0045] [(C) Thermosetting resin] The curable resin composition of the present invention is expected to have improved heat resistance by including a thermosetting resin. The thermosetting resin can be used alone or in combination of two or more. Any known thermosetting resin can be used. For example, known thermosetting resins such as amino resins such as melamine resins, benzoguanamine resins, melamine derivatives, and benzoguanamine derivatives, isocyanate compounds, blocked isocyanate compounds, cyclocarbonate compounds, epoxy compounds, oxetane compounds, episulfide resins, bismaleimides, and carbodiimide resins can be used. Particularly preferred is a thermosetting resin having a plurality of cyclic ether groups or cyclic thioether groups (hereinafter abbreviated as cyclic (thio)ether groups) in the molecule.
[0046] The thermosetting resin having a plurality of cyclic (thio)ether groups in the molecule is a compound having a plurality of 3-, 4-, or 5-membered cyclic (thio)ether groups in the molecule, and examples thereof include a compound having a plurality of epoxy groups in the molecule, i.e., a polyfunctional epoxy compound, a compound having a plurality of oxetanyl groups in the molecule, i.e., a polyfunctional oxetane compound, and a compound having a plurality of thioether groups in the molecule, i.e., an episulfide resin.
[0047] Examples of polyfunctional epoxy compounds include epoxidized vegetable oils, bisphenol A type epoxy resins, hydroquinone type epoxy resins, bisphenol type epoxy resins, thioether type epoxy resins, brominated epoxy resins, novolac type epoxy resins, biphenol novolac type epoxy resins, bisphenol F type epoxy resins, hydrogenated bisphenol A type epoxy resins, glycidylamine type epoxy resins, hydantoin type epoxy resins, alicyclic epoxy resins, trihydroxyphenylmethane type epoxy resins, bixylenol type or biphenol type epoxy resins, or mixtures thereof. ; bisphenol S type epoxy resin; bisphenol A novolac type epoxy resin; tetraphenylolethane type epoxy resin; heterocyclic epoxy resin; diglycidyl phthalate resin; tetraglycidyl xylenoylethane resin; naphthalene group-containing epoxy resin; epoxy resin having a dicyclopentadiene skeleton; glycidyl methacrylate copolymer epoxy resin; cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resin; epoxy-modified polybutadiene rubber derivative; CTBN-modified epoxy resin, etc., but are not limited thereto. These epoxy resins can be used alone or in combination of two or more. Among these, novolac type epoxy resin, bisphenol type epoxy resin, bixylenol type epoxy resin, biphenol type epoxy resin, biphenol novolac type epoxy resin, naphthalene type epoxy resin, or a mixture thereof is particularly preferred.
[0048] Examples of the polyfunctional oxetane compound include polyfunctional oxetanes such as bis[(3-methyl-3-oxetanylmethoxy)methyl]ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl]ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, (3-ethyl-3-oxetanyl)methyl acrylate, (3-methyl-3-oxetanyl)methyl methacrylate, (3-ethyl-3-oxetanyl)methyl methacrylate, and oligomers or copolymers thereof, as well as oxetane alcohols and novolac resins, poly(p-hydroxystyrene), cardo-type bisphenols, calixarenes, calixresoles, etc. Examples of the copolymer include ethers of synarenes and resins having a hydroxyl group, such as silsesquioxane, etc. In addition, examples of the copolymer include copolymers of unsaturated monomers having an oxetane ring and alkyl (meth)acrylates.
[0049] Examples of compounds having multiple cyclic thioether groups in the molecule include bisphenol A type episulfide resins. Also, episulfide resins in which the oxygen atoms of the epoxy groups of novolac type epoxy resins are replaced with sulfur atoms using a similar synthesis method can be used. The amount of such thermosetting resins having multiple cyclic (thio)ether groups in the molecule is preferably 0.6 to 2.5 equivalents of the cyclic (thio)ether groups relative to 1 equivalent of the alkali-soluble groups such as carboxyl groups and phenolic hydroxyl groups of the alkali-soluble resin (A), and more preferably 0.8 to 2.0 equivalents.
[0050] Examples of amino resins such as melamine derivatives and benzoguanamine derivatives include methylolmelamine compounds, methylolbenzoguanamine compounds, methylolglycoluril compounds, and methylolurea compounds.
[0051] As the isocyanate compound, a polyisocyanate compound can be blended. Examples of the polyisocyanate compound include aromatic polyisocyanates such as 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, naphthalene-1,5-diisocyanate, o-xylylene diisocyanate, m-xylylene diisocyanate and 2,4-tolylene dimer; aliphatic polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, methylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate; alicyclic polyisocyanates such as bicycloheptane triisocyanate; and adducts, biuret and isocyanurates of the above-mentioned isocyanate compounds.
[0052] The blocked isocyanate compound may be an addition reaction product of an isocyanate compound and an isocyanate blocking agent. Examples of isocyanate compounds that can react with an isocyanate blocking agent include the polyisocyanate compounds described above. Examples of isocyanate blocking agents include phenol-based blocking agents, lactam-based blocking agents, active methylene-based blocking agents, alcohol-based blocking agents, oxime-based blocking agents, mercaptan-based blocking agents, acid amide-based blocking agents, imide-based blocking agents, amine-based blocking agents, imidazole-based blocking agents, and imine-based blocking agents.
[0053] The thermosetting resin may be used alone or in combination of two or more. The amount of the thermosetting resin is preferably 20 to 60 parts by mass, more preferably 30 to 50 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When the amount is 20 parts by mass or more, the heat resistance is excellent. When the amount is 60 parts by mass or less, the storage stability is improved.
[0054] [(D) Colorant] The colorant may include one or more of red, green, blue, yellow, white, black, and other colorants in appropriate combination. Any of pigments, dyes, and colorants may be used. Specific examples include those having a Color Index (CI; published by The Society of Dyers and Colourists) number. However, from the viewpoint of reducing environmental load and effects on the human body, it is preferable that the colorant does not contain halogen.
[0055] Examples of red colorants include monoazo-based, diazazol-based, azo lake-based, benzimidazolone-based, perylene-based, diketopyrrolopyrrole-based, condensed azo-based, anthraquinone-based, and quinacridone-based. Green colorants include metal-substituted or unsubstituted phthalocyanines, anthraquinones, and perylenes. The blue colorant may be any of pigments, dyes, and coloring matter, but among them, those that do not contain halogen atoms are preferred. Blue colorants include phthalocyanine-based and anthraquinone-based, and the pigment-based compounds are classified as pigments, specifically, the following can be mentioned: Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:6, 16, 60. As the dye-based compounds, Solvent Blue 35, 63, 68, 70, 83, 87, 94, 97, 122, 136, 67, 70, etc. can be used. In addition to the above, metal-substituted or unsubstituted phthalocyanine compounds can also be used. The blue colorant may be used alone or in combination of two or more. Yellow colorants include monoazo-based, disazo-based, condensed azo-based, benzimidazolone-based, isoindolinone-based, and anthraquinone-based agents. Examples of the white colorant include rutile type and anatase type titanium oxide. Examples of black colorants include titanium black, carbon black, graphite, iron oxide, anthraquinone, cobalt oxide, copper oxide, manganese oxide, antimony oxide, nickel oxide, perylene, and aniline pigments, molybdenum sulfide, and bismuth sulfide. In addition, colorants such as purple, orange, brown, etc. may be added to adjust the color tone. In order to obtain an alkali-developable curable resin composition having excellent resolution and in which the coating film formed on copper after the CZ treatment has excellent hiding power and thus undergoes little change in color after heating, it is preferable to use a combination of a red colorant, a yellow colorant, a blue colorant, and a black colorant as the colorant. In this case, the blending amounts of the (D) colorant, relative to 100 parts by mass of the solid content of the (A) alkali-soluble resin, are preferably within the ranges of 0.01 to 0.04 parts by mass of the black colorant, 1.10 to 2.45 parts by mass of the blue colorant, 0.01 to 0.08 parts by mass of the yellow colorant, and 0.60 to 2.00 parts by mass of the red colorant, and more preferably within the ranges of 0.02 to 0.03 parts by mass of the black colorant, 1.40 to 2.20 parts by mass of the blue colorant, 0.03 to 0.06 parts by mass of the yellow colorant, and 0.75 to 1.20 parts by mass of the red colorant.
[0056] [Inorganic filler] The curable resin composition of the present invention preferably contains an inorganic filler. The inorganic filler is not particularly limited, and may be one or more of known and commonly used inorganic fillers, such as silica, crystalline silica, Neuburg silica, aluminum hydroxide, glass powder, talc, clay, magnesium carbonate, calcium carbonate, natural mica, synthetic mica, aluminum hydroxide, barium sulfate, barium titanate, iron oxide, non-fibrous glass, hydrotalcite, mineral wool, aluminum silicate, calcium silicate, and zinc oxide. Among them, silica is preferred, and spherical silica is more preferred because it has a small surface area and the stress is distributed throughout, making it less likely to become the starting point of cracks.
[0057] The inorganic filler may be surface-treated. Here, the surface treatment of the inorganic filler refers to a treatment for improving compatibility with the resin component. The surface treatment of the inorganic filler may be either a surface treatment capable of introducing a curable reactive group to the surface of the inorganic filler or a surface treatment not capable of introducing a curable reactive group. Here, the curable reactive group is not particularly limited as long as it is a group that undergoes a curing reaction with a curable compound such as (A) an alkali-soluble resin or (C) a thermosetting resin, and may be a curable reactive group or a thermosetting reactive group. Examples of the curable reactive group include a methacryl group, an acrylic group, a vinyl group, and a styryl group, and examples of the thermosetting reactive group include an epoxy group, an amino group, a hydroxyl group, a carboxyl group, an isocyanate group, an imino group, an oxetanyl group, a mercapto group, a methoxymethyl group, a methoxyethyl group, an ethoxymethyl group, an ethoxyethyl group, and an oxazoline group. The method of introducing a curable reactive group into the surface of the inorganic filler is not particularly limited, and may be introduced using a known, commonly used method, and the surface of the inorganic filler may be treated with a surface treatment agent having a curable reactive group, such as a coupling agent having a curable reactive group as an organic group. As the coupling agent, a silane coupling agent, a titanium coupling agent, a zirconium coupling agent, an aluminum coupling agent, etc. may be used. In addition, examples of surface-treated inorganic fillers that do not have a curable reactive group include inorganic fillers that have been subjected to silica-alumina surface treatment, titanate-based coupling agent treatment, aluminate-based coupling agent treatment, and organic treatment.
[0058] The inorganic filler may be used alone or in combination of two or more. The amount of the inorganic filler is preferably 80 to 450 parts by mass, more preferably 100 to 200 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When it is 80 parts by mass or more, the heat resistance is excellent. When it is 450 parts by mass or less, the resolution is more excellent.
[0059] (Compound having an ethylenically unsaturated group) The curable resin composition of the present invention may contain a substance that functions as a reactive diluent, specifically a compound having an ethylenically unsaturated group, unlike the alkali-soluble resin (A). As the compound having an ethylenically unsaturated group, a photopolymerizable oligomer, a photopolymerizable vinyl monomer, etc., which are known and commonly used photocurable monomers, may be used.
[0060] Examples of the photopolymerizable oligomer include unsaturated polyester oligomers and (meth)acrylate oligomers. Examples of the (meth)acrylate oligomer include epoxy (meth)acrylates such as phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and bisphenol type epoxy (meth)acrylate. acrylate, urethane (meth)acrylate, epoxy urethane (meth)acrylate, polyester (meth)acrylate, polyether (meth)acrylate, polybutadiene-modified (meth)acrylate, etc.
[0061] Examples of the photopolymerizable vinyl monomer include known and commonly used ones, for example, styrene derivatives such as styrene, chlorostyrene, and α-methylstyrene; vinyl esters such as vinyl acetate, vinyl butyrate, and vinyl benzoate; vinyl ethers such as vinyl isobutyl ether, vinyl-n-butyl ether, vinyl-t-butyl ether, vinyl-n-amyl ether, vinyl isoamyl ether, vinyl-n-octadecyl ether, vinyl cyclohexyl ether, ethylene glycol monobutyl vinyl ether, and triethylene glycol monomethyl vinyl ether; (meth)acrylamides such as acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and N-butoxymethyl acrylamide; allyl compounds such as triallyl isocyanurate, diallyl phthalate, and diallyl isophthalate; 2-ethylhexyl (meth)acrylate, lauryl ( (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate and other (meth)acrylic acid esters; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate and other hydroxyalkyl (meth)acrylates; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate and other alkoxyalkylene glycol mono(meth)acrylates; ethylene glycol di(meth)acrylate, butanediol di(meth)acrylates, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate and other alkylene polyol poly(meth)acrylates;Examples of the polyoxyalkylene glycol poly(meth)acrylates include diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, ethoxylated trimethylolpropane triacrylate, and propoxylated trimethylolpropane tri(meth)acrylate; poly(meth)acrylates such as hydroxypivalic acid neopentyl glycol ester di(meth)acrylate; and isocyanurate-type poly(meth)acrylates such as tris[(meth)acryloxyethyl]isocyanurate. These may be used alone or in combination of two or more types according to the required properties.
[0062] The compound having an ethylenically unsaturated group may be used alone or in combination of two or more. The amount of the compound having an ethylenically unsaturated group is preferably 3 to 25 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When it is 3 parts by mass or more, it contributes to high sensitivity. When it is 25 parts by mass or less, the resolution is improved.
[0063] (Thermosetting catalyst) The curable resin composition of the present invention may contain a heat curing catalyst. Examples of such heat curing catalysts include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; and hydrides such as adipic acid dihydrazide and sebacic acid dihydrazide. Examples of the compound include arylazine compounds and phosphorus compounds such as triphenylphosphine. In addition, S-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-S-triazine, 2-vinyl-2,4-diamino-S-triazine, 2-vinyl-4,6-diamino-S-triazine·isocyanuric acid adduct, and 2,4-diamino-6-methacryloyloxyethyl-S-triazine·isocyanuric acid adduct can also be used, and preferably, these compounds that also function as adhesion-imparting agents are used in combination with the thermosetting catalyst. In addition, organic fillers may be used as long as they can be used as a thermosetting catalyst.
[0064] As the thermosetting catalyst, an organic filler having an amino group is preferable, and specifically, at least one of melamine and dicyandiamide (DICY) is preferable.
[0065] The thermosetting catalyst may be used alone or in combination of two or more. The amount of the thermosetting catalyst is preferably 0.5 to 10 parts by mass, more preferably 1 to 8 parts by mass, per 100 parts by mass of the solid content of the alkali-soluble resin (A). When the amount is 0.5 parts by mass or more, the heat resistance is excellent. When the amount is 10 parts by mass or less, the storage stability is improved.
[0066] (Organic solvent) The curable resin composition of the present invention may contain an organic solvent for the purpose of adjusting the viscosity when preparing the composition or when applying it to a substrate or a carrier film. Examples of the organic solvent include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. Known and commonly used organic solvents can be used. These organic solvents can be used alone or in combination of two or more.
[0067] (Other optional ingredients) Furthermore, the curable resin composition of the present invention may contain other curing components and other additives that are well known and commonly used in the field of electronic materials. Examples of other curing components include cyanate ester resins, active ester resins, maleimide compounds, and alicyclic olefin polymers. Examples of other additives include thermal polymerization inhibitors, ultraviolet absorbers, silane coupling agents, plasticizers, flame retardants, antistatic agents, antiaging agents, antibacterial and antifungal agents, defoamers, leveling agents, thickeners, adhesion agents, thixotropy agents, photoinitiator assistants, sensitizers, thermoplastic resins, organic fillers, release agents, surface treatment agents, dispersants, dispersion assistants, surface modifiers, stabilizers, and phosphors.
[0068] The curable resin composition of the present invention may be used in the form of a dry film or in the form of a liquid. When used in the form of a liquid, it may be a one-component type or a two-component or more type.
[0069] Next, the dry film of the present invention has a resin layer obtained by applying and drying the curable resin composition of the present invention on a carrier film. When forming a dry film, first, the curable resin composition of the present invention is diluted with the organic solvent to adjust the viscosity to an appropriate level, and then coated on a carrier film to a uniform thickness using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, or the like. Thereafter, the applied composition is usually dried at a temperature of 40 to 130°C for 1 to 30 minutes to form a resin layer. There is no particular restriction on the coating thickness, but it is generally appropriately selected within the range of 3 to 150 μm, preferably 5 to 60 μm, in terms of the film thickness after drying.
[0070] As the carrier film, a plastic film is used, and for example, a polyester film such as polyethylene terephthalate (PET), a polyimide film, a polyamideimide film, a polypropylene film, a polystyrene film, etc. can be used. There is no particular restriction on the thickness of the carrier film, but it is generally appropriately selected in the range of 10 to 150 μm. It is more preferably in the range of 15 to 130 μm.
[0071] After forming a resin layer made of the curable resin composition of the present invention on a carrier film, it is preferable to further laminate a peelable cover film on the surface of the resin layer for the purpose of preventing dust from adhering to the surface of the resin layer. For example, a polyethylene film, a polytetrafluoroethylene film, a polypropylene film, a surface-treated paper, etc. can be used as the peelable cover film. The cover film may be any film that has a smaller adhesive force than that between the resin layer and the carrier film when the cover film is peeled off.
[0072] In the present invention, the curable resin composition of the present invention may be applied to the cover film and dried to form a resin layer, and a carrier film may be laminated on the surface of the resin layer. That is, in the present invention, either a carrier film or a cover film may be used as the film to which the curable resin composition of the present invention is applied when producing a dry film.
[0073] The printed wiring board of the present invention has a cured product obtained from the resin layer of the curable resin composition or dry film of the present invention. As a method for producing the printed wiring board of the present invention, for example, the curable resin composition of the present invention is adjusted to a viscosity suitable for the coating method using the organic solvent, and applied to a substrate by a method such as dip coating, flow coating, roll coating, bar coating, screen printing, or curtain coating, and then the organic solvent contained in the composition is evaporated and dried (temporarily dried) at a temperature of 60 to 100 ° C. to form a tack-free resin layer. In addition, in the case of a dry film, the resin layer is attached to the substrate by a laminator or the like so that the resin layer contacts the substrate, and then the carrier film is peeled off to form a resin layer on the substrate.
[0074] The above-mentioned substrates include printed wiring boards and flexible printed wiring boards on which circuits have been formed in advance using copper or the like, as well as materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, copper-clad laminates for high-frequency circuits made from fluororesin, polyethylene, polyphenylene ether, polyphenylene oxide, cyanate, etc., including copper-clad laminates of all grades (FR-4, etc.), as well as metal substrates, polyimide films, PET films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafer plates, etc.
[0075] The volatilization drying carried out after application of the curable resin composition of the present invention can be carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven, or the like (a method in which hot air in a dryer equipped with a heat source of an air heating method using steam is brought into countercurrent contact with the substrate, or a method in which hot air is blown onto the substrate from a nozzle).
[0076] After forming a resin layer on a substrate, the resin layer is selectively exposed to active energy rays through a photomask with a predetermined pattern, and the unexposed areas are developed with a dilute alkaline aqueous solution (e.g., 0.3 to 3 mass% sodium carbonate aqueous solution) to form a pattern of a cured product. The cured product is then irradiated with active energy rays and then heat-cured (e.g., 100 to 220°C), or is irradiated with active energy rays after heat-curing, or is heat-cured only to form a final finish curing (main curing) to form a cured film with excellent properties such as adhesion and hardness. When the curable resin composition of the present invention contains a photobase generator, it is preferable to heat the composition after exposure and before development. The heating conditions after exposure and before development are preferably, for example, heating at 60 to 150° C. for 1 to 60 minutes.
[0077] The exposure machine used for the above-mentioned active energy ray irradiation may be a machine equipped with a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, or the like, and capable of irradiating ultraviolet rays in the range of 350 to 450 nm. Furthermore, a direct imaging machine (for example, a laser direct imaging machine that directly draws an image with a laser based on CAD data from a computer) may also be used. The lamp light source or laser light source of the direct imaging machine may have a maximum wavelength in the range of 350 to 450 nm. The exposure dose for forming an image varies depending on the film thickness, etc., but is generally 10 to 1000 mJ / cm. 2 , preferably 20 to 800 mJ / cm 2 The range may be:
[0078] The developing method can be a dipping method, a shower method, a spray method, a brush method, or the like, and the developing solution can be an aqueous alkali solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, or the like.
[0079] The curable resin composition of the present invention is preferably used to form a cured film on a printed wiring board, more preferably used to form a permanent coating film, and even more preferably used to form a solder resist, an interlayer insulating layer, and a coverlay. In addition, the curable resin composition of the present invention can obtain a cured product that is excellent in appearance and surface smoothness even when thin, and has excellent sensitivity and resolution, so that it can be preferably used to form a printed wiring board that requires high reliability in a thin film, such as a package substrate, especially a permanent coating film (particularly a solder resist) for FC-BGA.
[0080] In particular, the curable resin composition of the present invention can be suitably used for forming a thin cured film having a thickness of preferably 3 to 40 μm, and more preferably 5 to 30 μm. EXAMPLES
[0081] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following, "parts" and "%" are all based on mass unless otherwise specified.
[0082] (Synthesis of alkali-soluble resin A-1) Into an autoclave equipped with a thermometer, a nitrogen introduction device / alkylene oxide introduction device, and a stirrer, 119.4 parts of cresol novolac resin (Shonoru CRG-951 manufactured by Aica Kogyo Co., Ltd., OH equivalent: 119.4), 1.19 parts of potassium hydroxide, and 119.4 parts of toluene were introduced, and the system was replaced with nitrogen while stirring, and heated to increase the temperature. Next, 63.8 parts of propylene oxide were gradually added dropwise, and the temperature was increased to 125-132°C and 0-4.8 kg / cm. 2The mixture was reacted at 100°C for 16 hours. After that, the mixture was cooled to room temperature, and 1.56 parts of 89% phosphoric acid was added to the reaction solution to neutralize the potassium hydroxide, and a propylene oxide reaction solution of novolac cresol resin with a non-volatile content of 62.1% and a hydroxyl value of 182.2 mgKOH / g (307.9 g / eq.) was obtained. This was a mixture in which 1.08 moles of propylene oxide was added on average per equivalent of phenolic hydroxyl group. 293.0 parts of the propylene oxide reaction solution of novolac cresol resin, 43.2 parts of acrylic acid, 11.53 parts of methanesulfonic acid, 0.18 parts of methylhydroquinone, and 252.9 parts of toluene were introduced into a reactor equipped with a stirrer, a thermometer, and an air inlet tube, and the mixture was reacted at 110°C for 12 hours while being stirred and air was blown in at a rate of 10 ml / min. The water produced by the reaction was an azeotropic mixture with toluene, and 12.6 parts of water were distilled out. After that, the reaction solution was cooled to room temperature, neutralized with 35.35 parts of 15% aqueous sodium hydroxide solution, and then washed with water. Then, the toluene was distilled off while being replaced with 118.1 parts of diethylene glycol monoethyl ether acetate in an evaporator, and a novolac type acrylate resin solution was obtained. Next, 332.5 parts of the obtained novolac type acrylate resin solution and 1.22 parts of triphenylphosphine were introduced into a reactor equipped with a stirrer, a thermometer, and an air blowing tube, and air was blown in at a rate of 10 ml / min. While stirring, 60.8 parts of tetrahydrophthalic anhydride was gradually added, reacted at 95 to 101 ° C. for 6 hours, cooled, and then taken out. In this way, a solution of acrylate resin A-1 with a solid content of 65% and an acid value of the solid content of 87.7 mg KOH / g was obtained.
[0083] (Synthesis of alkali-soluble resin A-2) In a flask equipped with a cooling tube and a stirrer, 456 parts of bisphenol A, 228 parts of water, and 649 parts of 37% formalin were charged, and the temperature was kept below 40°C, and 228 parts of 25% aqueous sodium hydroxide solution was added. After the addition was completed, the mixture was reacted at 50°C for 10 hours. After the reaction was completed, the mixture was cooled to 40°C, and neutralized to pH 4 with 37.5% aqueous phosphoric acid solution while keeping the temperature below 40°C. The mixture was then left to stand and the aqueous layer was separated. After the separation, 300 parts of methyl isobutyl ketone was added and dissolved uniformly, and the mixture was washed three times with 500 parts of distilled water, and water, solvent, etc. were removed under reduced pressure at a temperature below 50°C. The obtained polymethylol compound was dissolved in 550 parts of methanol to obtain 1230 parts of a methanol solution of the polymethylol compound. A part of the obtained methanol solution of the polymethylol compound was dried at room temperature in a vacuum dryer, and the solid content was 55.2%. 500 parts of the resulting methanol solution of the polymethylol compound and 440 parts of 2,6-xylenol were charged and uniformly dissolved at 50°C. After uniform dissolution, methanol was removed under reduced pressure at a temperature of 50°C or less. Then, 8 parts of oxalic acid were added and reacted at 100°C for 10 hours. After the reaction was completed, the distillate was removed under reduced pressure of 180°C and 50 mmHg to obtain 550 parts of novolak resin A. Furthermore, 130 parts of the above novolak resin A, 2.6 parts of a 50% aqueous sodium hydroxide solution, and 100 parts of toluene / methyl isobutyl ketone (mass ratio = 2 / 1) were charged into an autoclave equipped with a thermometer, a nitrogen introducing device / alkylene oxide introducing device, and a stirrer, and the inside of the system was replaced with nitrogen while stirring, and then heated to a temperature of 150°C and 8 kg / cm. 2 45 parts of ethylene oxide was gradually introduced and reacted at a gauge pressure of 0.0 kg / cm. 2The reaction was continued for about 4 hours until the reaction solution became 3.3 parts of 36% hydrochloric acid aqueous solution, and then the sodium hydroxide was neutralized. The neutralized reaction product was diluted with toluene, washed with water three times, and the solvent was removed using an evaporator to obtain an ethylene oxide adduct of novolac resin A having a hydroxyl value of 175 g / eq. This product had an average of 1 mole of ethylene oxide added per equivalent of phenolic hydroxyl group. 175 parts of the ethylene oxide adduct of novolac resin A thus obtained, 50 parts of acrylic acid, 3.0 parts of p-toluenesulfonic acid, 0.1 parts of hydroquinone monomethyl ether, and 130 parts of toluene were charged into a reactor equipped with a stirrer, thermometer, and air blowing tube, and the mixture was stirred while blowing in air, heated to 115°C, and reacted for another 4 hours while distilling off the water generated by the reaction as an azeotropic mixture with toluene, and then cooled to room temperature. The resulting reaction solution was washed with a 5% aqueous NaCl solution, and the toluene was removed by distillation under reduced pressure. Diethylene glycol monoethyl ether acetate was then added to obtain an acrylate resin solution with a solid content of 68%. Next, 312 parts of the obtained acrylate resin solution, 0.1 parts of hydroquinone monomethyl ether, and 0.3 parts of triphenylphosphine were charged into a four-neck flask equipped with a stirrer and a reflux condenser, and the mixture was heated to 110°C, 45 parts of tetrahydrophthalic anhydride were added, reacted for 4 hours, cooled, and then removed. The carboxyl group-containing photosensitive resin thus obtained had a non-volatile content of 72% and a solid acid value of 65 mgKOH / g. Hereinafter, this solution of the carboxyl group-containing photosensitive resin is referred to as A-2 varnish.
[0084] (Synthesis of alkali-soluble resin A-3) In a flask equipped with a cooling tube and a stirrer, 456 parts of bisphenol A, 228 parts of water, and 649 parts of 37% formalin were charged, and the temperature was kept below 40°C, and 228 parts of 25% aqueous sodium hydroxide solution was added. After the addition was completed, the mixture was reacted at 50°C for 10 hours. After the reaction was completed, the mixture was cooled to 40°C, and neutralized to pH 4 with 37.5% aqueous phosphoric acid solution while keeping the temperature below 40°C. The mixture was then left to stand and the aqueous layer was separated. After the separation, 300 parts of methyl isobutyl ketone was added and dissolved uniformly, and the mixture was washed three times with 500 parts of distilled water, and water, solvent, etc. were removed under reduced pressure at a temperature below 50°C. The obtained polymethylol compound was dissolved in 550 parts of methanol to obtain 1230 parts of a methanol solution of the polymethylol compound. A part of the obtained methanol solution of the polymethylol compound was dried at room temperature in a vacuum dryer, and the solid content was 55.2%. 500 parts of the resulting methanol solution of the polymethylol compound and 440 parts of 2,6-xylenol were charged and uniformly dissolved at 50°C. After uniform dissolution, methanol was removed under reduced pressure at a temperature of 50°C or less. Then, 8 parts of oxalic acid were added and reacted at 100°C for 10 hours. After the reaction was completed, the distillate was removed under reduced pressure of 180°C and 50 mmHg to obtain 550 parts of novolak resin A. Furthermore, 130 parts of the above novolak resin A, 2.6 parts of a 50% aqueous sodium hydroxide solution, and 100 parts of toluene / methyl isobutyl ketone (mass ratio = 2 / 1) were charged into an autoclave equipped with a thermometer, a nitrogen introducing device / alkylene oxide introducing device, and a stirrer, and the inside of the system was replaced with nitrogen while stirring, and then heated to a temperature of 150°C and 8 kg / cm. 2 45 parts of ethylene oxide was gradually introduced and reacted at a gauge pressure of 0.0 kg / cm. 2The reaction was continued for about 4 hours until the reaction solution became 3.3 parts of 36% hydrochloric acid aqueous solution, and then the sodium hydroxide was neutralized. The neutralized reaction product was diluted with toluene, washed with water three times, and desolvated with an evaporator to obtain an ethylene oxide adduct of novolac resin A having a hydroxyl value of 175 g / eq. This product had an average of 1 mole of ethylene oxide added per equivalent of phenolic hydroxyl group. 175 parts of the ethylene oxide adduct of novolac resin A thus obtained, 75 parts of methacrylic acid, 3.0 parts of p-toluenesulfonic acid, 0.1 parts of hydroquinone monomethyl ether, and 130 parts of toluene were charged into a reactor equipped with a stirrer, thermometer, and air blowing tube, and the mixture was stirred while blowing in air, heated to 115°C, and reacted for another 4 hours while distilling off the water generated by the reaction as an azeotropic mixture with toluene, and then cooled to room temperature. The resulting reaction solution was washed with a 5% NaCl aqueous solution, and the toluene was removed by vacuum distillation. Diethylene glycol monoethyl ether acetate was then added to obtain an acrylate resin solution with a solid content of 68%. Hereinafter, this acrylate resin solution is referred to as resin solution A-3.
[0085] (Synthesis of spherical silica) An inorganic filler was obtained by mixing and dispersing 70 g of spherical silica (SFP-30M manufactured by Denka) and 30 g of PMA (propylene glycol monomethyl ether acetate) as a solvent.
[0086] [Examples and Comparative Examples] The components were mixed in the ratios (parts by mass) shown in Table 1, premixed with a stirrer, and then kneaded with a bead mill to prepare curable resin compositions. The amounts in the table indicate the solid content (non-volatile content).
[0087] (Preparation of dry film) The above prepared curable resin composition was applied onto a PET film with an applicator so that the resin layer after drying had a predetermined thickness, and then dried at 80° C. for 30 minutes to obtain a dry film.
[0088] (transmittance) According to the method described in (Preparation of Dry Film) above, a dry film having a resin layer thickness of 20 μm after drying was prepared. The dry film having a resin layer thickness of 20 μm was laminated on a glass substrate having a thickness of 2 mm, and the PET film was peeled off. Then, the absorbance was measured using a spectrophotometer V-670.
[0089] (Concealment) According to the method described in (Preparation of Dry Film) above, dry films with resin layer thicknesses of 20 μm and 25 μm after drying were prepared. Next, 18 μm copper foil was CZ-treated (roughening treatment) at an etching rate of 1 μm using MEC Etch Bond CZ-8101 manufactured by MEC Co., Ltd., and further anti-rust-treated using MEC Etch Bond CL-8300 manufactured by MEC Co., Ltd., and each dry film was laminated on a printed wiring board with a Cu thickness of 17 μm and a comb pattern of L / S=12 μm / 13 μm. For this, exposure was performed on the entire surface with an optimal exposure amount of 800 mJ using HMW680GW (metal halide lamp, scattered light) manufactured by Oak Manufacturing Co., Ltd. After peeling off the PET film, the film was further irradiated with ultraviolet light with an integrated exposure amount of 1000 mJ, and then heated at 160 ° C for 60 minutes in a heat circulation box furnace to harden (post cure). The printed wiring board having the resulting cured film was visually evaluated for its concealment of the circuit. ◎: The Cu circuit is completely invisible in both the 20 μm and 25 μm cured films. ◯: The Cu circuit is visible through the 20 μm cured film, but the Cu circuit is completely invisible through the 25 μm cured film. ×: The Cu circuit is visible through both the 20 μm and 25 μm cured films.
[0090] (Resolution) According to the method described in (Preparation of Dry Film) above, a dry film with a resin layer thickness of 20 μm after drying was prepared. A 35 μm copper foil was CZ-treated (roughening treatment) at an etching rate of 1 μm using MEC Etch Bond CZ-8101 manufactured by MEC Co., Ltd., and furthermore, a 34 μm copper foil was rust-proofed using MEC Etch Bond CL-8300 manufactured by MEC Co., Ltd. A dry film with a resin layer thickness of 20 μm was laminated on a substrate, and exposed to light using a projection exposure machine UFX-2223M-APU01 that cuts off the longer wavelength side than i-line so as to have an opening pattern with a diameter of 40 to 350 nm. The PET film was peeled off and developed with a 1.0 wt% sodium carbonate aqueous solution, and the minimum opening diameter that could be formed was confirmed by SEM. ○: Minimum diameter is 40 μm or less ×: Minimum diameter is more than 40 μm
[0091] (Color change confirmation test) According to the method described in (Preparation of Dry Film) above, a dry film with a resin layer thickness of 20 μm after drying was prepared. A 35 μm copper foil was CZ-treated (roughening treatment) at an etching rate of 1 μm using MEC Etch Bond CZ-8101 manufactured by MEC Co., Ltd., and furthermore, a 34 μm copper foil was rustproofed using MEC Etch Bond CL-8300 manufactured by MEC Co., Ltd. The dry film with a resin layer thickness of 20 μm was laminated on the substrate. This was exposed to light over the entire surface with an optimal exposure dose of 800 mJ using an HMW680GW (metal halide lamp, scattered light) manufactured by Oak Seisakusho Co., Ltd. After peeling off the PET film, ultraviolet light was further irradiated with an integrated exposure dose of 1000 mJ. The color change confirmation test was performed on the substrate after irradiation with ultraviolet light in a thermal circulation box furnace under two conditions: 150°C, 60 minutes post-cure, and 170°C, 60 minutes post-cure. The color change was measured using a Konica Minolta CM-2600d colorimeter in SCI mode using the CIE L * a * b * The measurement was performed by the method.
[0092] [Table 1]
[0093] The notes in the headings of Table 1 are as follows: *1: Alkali-soluble resin A-1 synthesized above *2: Alkali-soluble resin A-2 synthesized above *3: Alkali-soluble resin A-3 synthesized above *4: Sanyo Chemical Industries, Ltd. Neomer DA-600 *5: BASF Japan Laromer LR8863 *6: DIC N-870-75EA *7: NC-3000H manufactured by Nippon Kayaku Co., Ltd. *8: DIC HP-7200L *9: CI Pigment red 149 *10: CI Pigment yellow 147 *11: Phthalocyanine blue (CI Pigment blue 15) *12: Carbon black *13: Sakai Chemical Industry Co., Ltd. B-30 *14: Spherical silica synthesized above *15: IGM Resins Omnirad TPO H, acylphosphine oxide photopolymerization initiator *16: JMT-784 manufactured by DKSH Japan, a titanocene-based photopolymerization initiator *17: Melamine *18:DICY (Dicyandiamide) *19: Kawasaki Kasei Kinopower QS-30
[0094] From the results shown in the above table, it can be seen that the curable resin composition of the present invention is excellent in hiding power and resolution. In contrast, Comparative Example 1 had a poor hiding power evaluation result. Comparative Examples 2 and 3 had a poor resolution evaluation result. Comparative Example 4 had a poor hiding power evaluation result. Comparative Examples 5, 6, and 7 had a poor resolution evaluation result. In addition, in Examples 1 to 4 and Comparative Example 3, changes in color tone were observed before and after heating. Note that Comparative Examples 1 and 4 had poor hiding power evaluation results, and Comparative Examples 2, 5, 6, and 7 had poor resolution evaluation results, so no changes in color tone were observed. As a result, in Examples 1 to 4, the color change before and after heating was small, whereas in Comparative Example 3, the color change was large compared to Examples 1 to 4. Although not shown in the table, a composition was prepared as Comparative Example 8 in which the components other than the pigment were blended in the same amounts as in Comparative Example 2, but the pigment did not contain black, yellow, or red, and only blue was blended in at 1.89 parts by mass. When the resolution of Comparative Example 8 was evaluated, it was improved to 30 μm, but the evaluation result of the hiding power was x, so no other evaluations were performed.
Claims
1. A curable resin composition comprising (A) an alkali-soluble resin, (B) a photopolymerization initiator, (C) a thermosetting resin, and (D) a colorant, the curable resin composition being formed on copper having a CZ-treated surface, The (D) colorant contains a red colorant, a blue colorant, a yellow colorant and a black colorant, A curable resin composition, characterized in that a dry coating film (film thickness 20 μm) of the curable resin composition formed on a glass substrate having a thickness of 2 mm has a transmittance of 5% or more at a wavelength of 365 nm, 30 to 50% at a wavelength of 430 nm, 28 to 45% at a wavelength of 530 nm, and 12% or less at a wavelength of 720 nm.
2. A dry film comprising a resin layer obtained from the curable resin composition according to claim 1.
3. A cured product obtained by curing the curable resin composition according to claim 1 or the resin layer of the dry film according to claim 2.
4. A printed wiring board comprising the cured product according to claim 3.
Citation Information
Patent Citations
Resist ink composition
JP1986243869A
Curable resin composition, dry film, cured product, and electronic component
JP2020057668A
Photosensitive resin composition, dry film and printed wiring board
WO2020045024A1